Psychological, psychiatric, and behavioral sciences measurement scales: best practice guidelines for their development and validation - Stefana, Alberto; Damiani, Stefano; Granziol, Umberto; Provenzani, Umberto; Solmi, Marco; Youngstrom, Eric A.; Fusar-Poli, Paolo (Frontiers in Psychology, 2025)
Psychiatric, psychological, and behavioral sciences scales provide quantitative representations of phenomena such as emotions, beliefs, functioning, and social role perceptions. Methodologists and researchers have criticized current scale development practices, emphasizing that inaccurate measurements can derail theory development and clinical decisions, thereby impeding progress in mental health research and practice. These shortcomings often stem from a lack of understanding of appropriate scale development techniques. This article presents a guide to scope, organize, and clarify the process of scale development and validation for psychological and psychiatric use by integrating current methodological literature with the authors’ real-world experience. The process is divided into five phases comprising 18 steps. In the Preliminary Phase, the need for a new scale is assessed, including a review of existing measures. In the Item Development Phase, the construct is defined, and an initial pool of items is generated, incorporating literature reviews, expert feedback, and target population evaluation to ensure item relevance and clarity. During the Scale Construction Phase, the scale is finalized through the administration of surveys to a large sample, followed by parallel analysis, exploratory factor, and item descriptive statistics to identify functional items. In the Scale Evaluation Phase, the dimensionality, reliability, and validity of the scale are rigorously tested using both classical and modern psychometric techniques. Finally, in the Finalization Phase, the optimal item sequence is decided, and a comprehensive inventory manual is prepared. In sum, this structured approach provides researchers and clinicians with a comprehensive methodology for developing reliable, valid, and user-friendly psychological, psychiatric, and behavioral sciences measurement scales.